x2-5x-6 as (x-3)( x-2)

Thank you for the opportunity to help you with your question!

x^2-5x-6

=x^2 +1x-6x -6

= x(x+1) -6(x+1)

=(x+1)(x-6)..............................answer

THIS IS THE CORRECT ANSWER ,we cannot write it into (x-3)( x-2)

and x= -1 or x= 6

Factor: X2-2x-8

X2-2x-8

(X-4)(x+2)

X-4=0, x+2=0

X=4, x=-2

What am I doing wrong here??

what you have done is correct

(x-4)(x+2)

x-4=0, x+2=0

x=4, x=-2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up